2017
DOI: 10.18203/2394-6040.ijcmph20173319
|View full text |Cite
|
Sign up to set email alerts
|

Management of diarrheal diseases among children under five years: a case study of mothers at Kakamega county, Kenya

Abstract: Background: Despite much effort and successes in the management of diarrhoea, the disease has remained among the top five causes of mortality and morbidity in Kenya, particularly among infants and children below five years. Advent of HIV/AIDS and the harsh economic situation is Kenya has led to increase in diarrhoea diseases. This study was conducted to determine the mother’s knowledge, attitude and practice in the management of diarrheal diseases among children under five years of age.Methods: This was a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, the analysis of childhood diarrhea and associated risk factors has become a concern all in both developed and developing countries. For instance, a number of studies in developing countries [16] [19] [20] [50] [51] have been carried out to study diarrhea disease among children under 5 years. However, most of them so far have focused exclusively on the risk factors that cause the disease and how the disease can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis of childhood diarrhea and associated risk factors has become a concern all in both developed and developing countries. For instance, a number of studies in developing countries [16] [19] [20] [50] [51] have been carried out to study diarrhea disease among children under 5 years. However, most of them so far have focused exclusively on the risk factors that cause the disease and how the disease can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…64 percent of those mothers who had attended hospital used ORS to control diarrhea of their children. 9 In the present study most of the mothers (21 out of 27) had applied ORS to control diarrhea of their children. The authors of another study about oral rehydration therapy had shown that 65.9 percent parents (313 out of 475) had used ORS during recent diarrheal episode of their children and 34.8 percent parents had perceived that ORS was intended to treat diarrhea and prevent dehydration.…”
Section: Discussionmentioning
confidence: 81%
“…5 Suitable hygiene education and proper hand washing can decrease the incidence of diarrhea by up to 45%. 6 In India, diarrheal disease poses a significant problem to the health, wellbeing and survival of children of less than five-year age group. It has a deleterious effect on growth and predisposes the child to malnutrition and other infections.…”
mentioning
confidence: 99%